2019
DOI: 10.1126/scisignal.aax9760
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rewiring of the hypertensive kidney

Abstract: Hypertension is a persistent epidemic across the developed world that is closely associated with kidney disease. Here, we applied a metabolomic, phosphoproteomic, and proteomic strategy to analyze the effect of hypertensive insults on kidneys. Our data revealed the metabolic aspects of hypertension-induced glomerular sclerosis, including lipid breakdown at early disease stages and activation of anaplerotic pathways to regenerate energy equivalents to counter stress. For example, branched-chain amino acids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…In a rat model of hypertension and proteinuria, increased metabolic stress was indicated by increased oxidized lipids derived from lipid breakdown in glomeruli at the early stage, causing decreased ATP and NADH levels. The change of metabolic aspects in glomeruli from these mice was associated with the activation of phosphoprotein-dependent signaling such as mTOR and AMPK (Rinschen et al, 2019). Steinberg et al demonstrated that AMPK activity is suppressed by TNFα signaling, resulting in decreased FA β-oxidation and excess lipids in skeletal muscle (Steinberg et al, 2006).…”
Section: Lipid Burden and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…In a rat model of hypertension and proteinuria, increased metabolic stress was indicated by increased oxidized lipids derived from lipid breakdown in glomeruli at the early stage, causing decreased ATP and NADH levels. The change of metabolic aspects in glomeruli from these mice was associated with the activation of phosphoprotein-dependent signaling such as mTOR and AMPK (Rinschen et al, 2019). Steinberg et al demonstrated that AMPK activity is suppressed by TNFα signaling, resulting in decreased FA β-oxidation and excess lipids in skeletal muscle (Steinberg et al, 2006).…”
Section: Lipid Burden and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…We had earlier reported a de cit of lysine metabolites in the kidney cortex in a hypertensive kidney disease model 22 . Based on these ndings, and on a potential bene cial role of lysine in the Framingham cohort 17 and 3 randomized controlled dietary intervention trials [18][19][20] , we hypothesized that administration of lysine can be helpful in a model of hypertensive kidney disease.…”
Section: Resultsmentioning
confidence: 93%
“…For untargeted metabolomic analysis, we used a UHPLC-MS approach. For fractionation, we used hydrophilic interaction liquid chromatography (HILIC) fractionation and reversed-phase (RP) chromatography as previously described 22 . We used a quadrupole time-of-ight instrument (Impact II, Bruker, Bremen, Germany) coupled to a ultrahigh-performance liquid chromatography (UHPLC) device (Bruker Elute, Bruker, Billerica, MA), or to an Agilent In nity 1290 UHPLC device (Agilent, USA).…”
Section: Metabolomics Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations